The Equilibrium Isotherm Removal OF Chromium From Waste Water By Aquatic Plants Using Batch Process Adsorption - Salman, M. S. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
This study was carried out in Baghdad (Al-Jadiriya) in 2006 by  detecting ability of aquatic reed plant to remove heavy metals (Chromium) from waste water by batch process of adsorption with considering that acidic solution is best selection for such process with constant initial chromium concentration(60 mg/l),speed of shaking(300 rpm), temperature (30 Co) and constant contact time (4 h) but with different weights of adsorbent (reed) (0.5 ,1 ,2 ,3 and 4 )gm for each 100 ml volume of sample .          The results showed that the percentage of the removed chromium were ( 8% ,17.5% ,31% ,40% and 50%) respectively for each sample according to the mass of adsorbent used. Equilibrium isotherm curve showed a good fitting with langmuir model and frendlich model with square regression value for both of them( R2 =0.93)  (R2 =0.97) respectively. The study results showed that aquatic reed plant can be used as an adsorbent to remove the pollutants from contaminated waste water.